PERBEDAAN PRESTASI BELAJAR ILMU PENGETAHUAN SOSIAL ANTAR KELAS PENDEKATAN CONTEXTUAL TEACHINGAND LEARNING DENGAN KELAS MODEL PEMBELAJARAN EKSPOSITORI - Amelia Astri Wulandari; AL. Sugijanto AL. Sugijanto (Universitas Sarjanawiyata Tamansiswa, 2017)
ABSTRACT This study aimed to know (1) the category of learning achievement of social science subject by using contextual teaching and learning, (2) the category of learning achievement of social science subject by using expository, and (3) the difference of learning achievement of social science subject by using contextual teaching and learning and expository. The type of this study was quasi experiment. Data collection techniques used documentation and test. Data analysis techniques used descriptive analysis and hypothesis testing by using Z test that was started by homogeneity variance and normality test. This study shows that (1) the category of learning achievement of social science subject by using contextual teaching and learning was in medium category with the mean sore 22.404 in the interval 21.35723.452. (2) The category of learning achievement of social science subject by using expository was in medium category with the mean score 20.451 in the interval 19.310 21.593. (3) Based on the analysis, the score of Zc = 4.73661 > Zt =1.65. It means that there was a positive and significant difference of learning achievement of social science subject by using contextual teaching and learning and expository.